2013
DOI: 10.1007/978-1-4614-7411-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tissue Oxygen Saturation Increases During the Night in Adolescents

Abstract: How does the oxygen metabolism change during sleep? We aimed to measure the change in brain tissue oxygen saturation (StO2) before and after sleep with near-infrared spectroscopy (NIRS) using an in-house developed sensor. According to the synaptic homeostasis hypothesis [1], synaptic downscaling during sleep would result in reduced energy consumption. Thus, this reduced energy demands should be reflected in the oxygen metabolism and StO2. Thirteen nights of 7 male subjects (age 11-16 years, one subject contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…112 This increase could also be linked to circadian effects, e.g., cortisol rhythm exerting its wake-promoting effect in the morning hours. 113,114 Moreover, the present findings indicated that the time of day has no significant influence on FCOA, which is in line with the literature. 115 It was also shown in this study that FCOA in StO 2 decreased with increasing room temperature.…”
Section: Environment and Certain Situational Variablesupporting
confidence: 92%
“…112 This increase could also be linked to circadian effects, e.g., cortisol rhythm exerting its wake-promoting effect in the morning hours. 113,114 Moreover, the present findings indicated that the time of day has no significant influence on FCOA, which is in line with the literature. 115 It was also shown in this study that FCOA in StO 2 decreased with increasing room temperature.…”
Section: Environment and Certain Situational Variablesupporting
confidence: 92%
“…Even, brain and muscle hemodynamics were compared in regard to different stages by fNIRS (Zhang and Khatami, 2015). In one study the oxygen saturation of the brain tissue after sleep was compared with the one prior to sleep (Metz et al, 2013). But there has been no comparison of brain oxygenation values of sleep stages between the beginning and end of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…However, the values depend on the specific characteristics of the input NIRS signals, e.g., number of MAs, frequency of occurrence of the MAs, amplitude of the MAs within the data, or the noise level. These parameters were chosen empirically to give the best result for the data sets comprising long-term NIRS measurements as reported by Metz et al [21,22]. ( ): unfiltered acceleration signal.…”
Section: Algorithmmentioning
confidence: 99%
“…Twelve healthy adolescent males (age 10-16 years) slept on two separate nights in the sleep laboratory of the University Children's Hospital Zurich, Switzerland. The mean sleep time was 8.5 h. The detailed protocol is described in Metz et al [21,22]. The study was approved by the ethical committee of the Canton of Zurich and informed consent was signed by the legal representatives of the adolescents.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation